Neurohospitalist Practice and Well-Being During the COVID-19 Pandemic. (October 2021) - Goyal, Tarini; Probasco, John C.; Gold, Carl A.; Klein, Joshua P.; Weathered, Natalie R.; Thakur, Kiran T.
Background and Purpose: Neurohospitalists play an important role in, and have been variably affected by, the ongoing COVID-19 pandemic. In this study, we survey neurohospitalists to characterize practice changes and the impact of the pandemic on their well-being. Methods: A 22-item survey was distributed to neurohospitalists through the Neurohospitalist Society and the American Academy of Neurology Neurohospitalist, Stroke & Vascular Neurology, and Critical Care & Emergency Neurology Sections. Results: After 2 weeks of collection, 123 responses were received, with 57% of respondents practicing in academic settings, 23% in private practice, and 7% in community hospitals. A minority of neurohospitalists (8%) were redeployed to care for COVID-19 or non-COVID-19 medicine patients. The most common neurologic diagnoses they reported in COVID-19 patients were delirium (85%), cerebrovascular events (75%), and seizure (35%); however, most neurohospitalists (59%) had evaluated fewer than 10 patients with COVID-19. Respondents observed that fewer patients with unrelated neurological diseases were admitted to the hospital compared to before the pandemic. Neurohospitalists experienced changes in administrative (27%), educational (15%), and research duties (11%), and had overall worse well-being and work-life balance (77%). Conclusions: The most common neurologic diagnoses seen in COVID-19 patients by neurohospitalists in this sample are delirium, cerebrovascular disease, and seizure. Though the majority of survey respondents reported not being primary frontline providers, they report key clinical and operational roles during the pandemic, and report worse well-being as compared to before the pandemic. Our data suggests that there are opportunities to improve neurohospitalists' experience through flexible work practices and providing family care support.